Synergic complement‐mediated bactericidal activity of monoclonal antibodies with distinct specificity. Issue 8 (17th June 2020) - Natali, Eriberto Noel; Principato, Silvia; Ferlicca, Francesca; Bianchi, Federica; Fontana, Lucia Eleonora; Faleri, Agnese; Pansegrau, Werner; Surdo, Paola Lo; Bartolini, Erika; Santini, Laura; Brunelli, Brunella; Giusti, Fabiola; et al.
Abstract: The classical complement pathway is triggered when antigen‐bound immunoglobulins bind to C1q through their Fc region. While C1q binds to a single Fc with low affinity, a higher avidity stable binding of two or more of C1q globular heads initiates the downstream reactions of the complement cascade ultimately resulting in bacteriolysis. Synergistic bactericidal activity has been demonstrated when monoclonal antibodies recognize nonoverlapping epitopes of the same antigen. The aim of the present work was to investigate the synergistic effect between antibodies directed toward different antigens. To this purpose, we investigated the bactericidal activity induced by combinations of monoclonal antibodies (mAbs) raised against factor H‐binding protein (fHbp) and Neisserial Heparin‐Binding Antigen (NHBA), two major antigens included in Bexsero, the vaccine against Meningococcus B, for prevention from this devastating disease in infants and adolescents. Collectively, our results show that mAbs recognizing different antigens can synergistically activate complement even when each single Mab is not bactericidal, reinforcing the evidence that cooperative immunity induced by antigen combinations can represent a remarkable added value of multicomponent vaccines. Our study also shows that the synergistic effect of antibodies is modulated by the nature of the respective epitopes, as well as by the antigen density on the bacterial cell surface.